PERKEMBANGAN KAWASAN WISATA PANTAI PULANG SYAWAL DI DESA TEPUS KABUPATEN GUNUNGKIDUL YOGYAKARTA - , Firzadi Anhar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Beach resorts in the Tepus Village, especially in Pulang Syawal Resort, is beach tourist area newly developed. At first an unspoiled beaches, untouched development. There is a good asphalt road access, white sand beaches and natural beach atmosphere makes private parties interested in building tourist facilities coast. The development of beach resorts have occurred since the entry of the private sector in 2009 and development continued to increase until 2012. The purpose of the study was to determine and analyze the spatial development and tourism development of Pulang Syawal Resort from 2009 to 2012 and factors that influence it. The study was conducted by qualitative inductive-deductive approach. The study was conducted in tourist areas of Pulang Syawal Resort and beach in Tepus Village, District Tepus, Gunungkidul Regency. The unit of information as a key figure is the investor (owner of Cafe Resto Indrayanti and other investors), local government (Department of Tourism and Cultural Regency of Gunungkidul and Tepus Village head) and Tepus villagers. The results showed that there has been a change in the use of space is \"Land of the Sultan\" (SG) and private community support facilities become tourist beaches. The development of spatial and tourism development of Pulang Syawal Resort at the end of the study period, based on the pattern of tourism development theory Miossec, in the year 2009 to the year 2010 is a phase 0-2 and in 2011- 2012, Phase 3 and 4. Based on the theory of evolution tour from Butler, in 2009- 2010 an exploration stage and in 2011-2012 is under development and construction. Internal factors which influence the development of the tourist area of Pulang Syawal Resort is a state and beach location, the price of land, the management investors and tourist organizations, beach tourism facilities and socio-economic motivation of local communities. Meanwhile, external factors that investors, tourism marketing and government policy. The dominant factor is the private sector. Based on the results of the study, formulated a descriptive model for the development of beach resorts of Pulang Syawal Resort and beaches in Gunungkidul is as follows: synergy between the role of stakeholders (local government, investors, local communities), spatial arrangement and development (SG land, beach border and tourist facilities), management area by involving stakeholders and good environmental management by creating landfills (garbage) travel and waste treatment. So the following year materialized beach resorts are clean, safe and comfortable.